Effect of Voltage on Gas Sensor Performance of Anodization Synthesized TiO2 Nanotubes Arrays - Faris, Mina Mohammed; Ayal, Asmaa Kadim (Iraqi Journal of Science, 2023)
Serious gases have been highly related to being prejudiced against human life within the environment. The evolution of a trustworthy gas sensor with an elevated response is of major importance for detecting various hazardous gases. Titanium dioxide (TiO2) nanotubes (TNTs) are favorable candidates with considerable potential and stellar performance in gas sensor applications. In this work, we have studied the effect of voltage on preparing TiO2 nanotubular arrays via the anodization technique for gas sensor applications. A simple electrochemical anodization approach was used to synthesize titanium dioxide nanotubes. Diverse techniques of characterization were used to evaluate TNTs. The results gained from field emission scanning electron microscopy (FESEM), energy dispersion spectroscopy (EDS), and X-ray diffraction (XRD) indicate that TiO2 was formed. Gas sensors were created, and the gas detection characteristics were directed towards hydrogen sulfide (H2S), which is not a healthy gas. The sensor made from these nanotubes responds well to this gas at different temperatures and has high sensitivity. The H2S-detecting characteristics were evaluated at values ranging from room temperature up to 300 oC. Results show that the gas sensor TNTs that was prepared at 30 volt for H2S gas sensing has the highest sensitivity and shortest response time at room temperature.